Skin Shows : Gothic Horror and the Technology of Monsters - Halberstam, Jack, 1961- (Book collections on Project MUSE., 1995)
In this examination of the monster as cultural object, Judith Halberstam offers a rereading of the monstrous that revises our view of the Gothic. Moving from the nineteenth century and the works of Shelley, Stevenson, Stoker, and Wilde to contemporary horror film exemplified by such movies as Silence of the Lambs, Texas Chainsaw Massacre, and Candyman, Skin Shows understands the Gothic as a versatile technology, a means of producing monsters that is constantly being rewritten by historically and culturally conditioned fears generated by a shared sense of otherness and difference. Deploying feminist and queer approaches to the monstrous body, Halberstam views the Gothic as a broad-based cultural phenomenon that supports and sustains the economic, social, and sexual hierarchies of the time. She resists familiar psychoanalytic critiques and cautions against any interpretive attempt to reduce the affective power of the monstrous to a single factor. The nineteenth-century monster is shown, for example, as configuring otherness as an amalgam of race, class, gender, and sexuality. Invoking Foucault, Halberstam describes the history of monsters in terms of its shifting relation to the body and its representations. As a result, her readings of familiar texts are radically new. She locates psychoanalysis itself within the gothic tradition and sees sexuality as a beast created in nineteenth century literature. Excessive interpretability, Halberstam argues, whether in film, literature, or in the culture at large, is the actual hallmark of monstrosity.